2019
DOI: 10.1158/1538-7445.am2019-3801
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3801: Reversing chemoresistance in high grade serous ovarian cancer

Abstract: Background: High grade serous ovarian cancer (HGSOC) is the most common ovarian cancer subtype. Although it is initially responsive to platinum-containing chemotherapy, the emergence of chemo-resistant cells is inevitable. Most women with HGSOC die of platinum-resistant cancer, and the five-year overall survival for ovarian cancer has changed little in recent decades. The aim of this project is to identify and validate existing, licensed drugs that selectively target resistant cancer cells in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of the observed discrepancies between prior art and the yeast platform can be explained by the comparatively high dynamic ranges on the yeast platform, which may have allowed it to pick up on DTIs that other screens might have missed. Chloroxine is known to bind OPRK1 [42], so based on phylogeny, it is not surprising that it also binds to OPRM1 as shown in our screen, despite the conflicting information from prior art. Activation of MTNR1A by serotonin has already been shown in other publications relying on yeast platforms [26, 43], however, this information is not deposited on either ChEMBL or the IUPHAR/BPS guide to pharmacology, which is why an older, and presumably less sensitive assay, is the only reference on this combination in the dataset[36].…”
Section: Discussionmentioning
confidence: 74%
“…Some of the observed discrepancies between prior art and the yeast platform can be explained by the comparatively high dynamic ranges on the yeast platform, which may have allowed it to pick up on DTIs that other screens might have missed. Chloroxine is known to bind OPRK1 [42], so based on phylogeny, it is not surprising that it also binds to OPRM1 as shown in our screen, despite the conflicting information from prior art. Activation of MTNR1A by serotonin has already been shown in other publications relying on yeast platforms [26, 43], however, this information is not deposited on either ChEMBL or the IUPHAR/BPS guide to pharmacology, which is why an older, and presumably less sensitive assay, is the only reference on this combination in the dataset[36].…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, expression of OPRK1, an opioid receptor that belongs to the superfamily of G protein-coupled opioid receptors, has been reported to be associated with a significantly poorer prognosis and tumour migration in various cancers, such as breast, oesophageal squamous cell carcinoma, metastatic liver cancer, and pancreas neuroendocrine tumours [ 57 , 58 ]. A recent in vitro study conducted with OPRK1 antagonist and agonist identified OPRK1 as mediator of chloroxine therapy, suggesting this target could be further exploited in combination with other chemotherapies [ 59 ]. Although these two targets did not progress in our validation pipeline, this was mostly due to limitations around availability of commercial antibodies against these proteins.…”
Section: Discussionmentioning
confidence: 99%